Regionales Klima und Gletscherschwankungen am Gran Campo Nevado, Patagonien - Schneider, Christoph (Zenodo, 2003)
English Abstract: The interdisciplinary project group 'Gran Campo Nevado' studied the regional climate and glacier mass balance in the Andes at 53°S in southwest Patagonia. For this purpose, climate data along a transect from west to east at 53°S of the two weather stations Faro Evangelistas and Punta Arenas Jorge Schythe and further own automatic weather stations (AWS) at Seno Skyring and Gran Campo Nevado were investigated. While the temperature regime is homogeneous with mesoscale modifications due to sea proximity and topography, there is an extreme gradient of precipitation from about 3,000 mm of precipitation on the west coast to about 6,000 mm of precipitation in the central channel and island zone to less than 500 mm of precipitation east of Punta Arenas. The AWS Gran Campo Nevado in the Puerto Bahamondes has been continuously recording climate data since October 1999. In the high oceanic climate found there, the annual sum of precipitation is 6,500 mm and the average annual temperature is +5.7°C at sea level. A semi-objective weather type classification for Patagonia and Tierra del Fuego was created from NCEP/NCAR reanalysis data. With only 10% of unclassified days, it shows a total of 10 different weather types. The weather type “west” with a zonal configuration and wind from the west takes the largest share with over 30%. Overall, weather situations with an inflow from the west occur on more than 60% of all days. All weather situations can be clearly distinguished on the basis of the average values of the climate elements at the individual weather stations. Particularly striking is the differentiation of precipitation, which at Gran Campo Nevado falls mainly with westerly inflow, while in Punta Arenas the largest share of precipitation falls with inflow from other sectors. This underlines the importance of the location, strength and persistence of the southern hemispheric westerly wind zone for the differentiation of precipitation in southwest Patagonia. A correlation analysis of different grid fields of NCEP/NCAR reanalysis data and the Southern Oscillation Index (SOI) shows a coupling between the El Niño Southern Oscillation (ENSO) and precipitation on the west side of the Andes between 50°S and 55°S. This is due to the decrease in the pressure gradient between the South Pacific anticyclone and the subpolar low pressure trough over the Bellingshausen Sea during El Niño. This is accompanied by a decrease in zonal wind speed and precipitation. This correlation, which leads to a reduction in precipitation on the west coast of approximately 10% to 20% during El Niño, can be demonstrated not only in the NCEP/NCAR data but also in precipitation data at the Faro Evangelistas weather station. At Gran Campo Nevado a digital terrain model and an orthophotomap of the southern part of the Península Muñoz Gamero with the ice cap of the Gran Campo Nevado was developed in the course of this study. This was the first time that the individual sub-glaciers of the ice cap and the other cirque glaciers of this part of the peninsula were inventoried for the World Glacier Monitoring Service (WGMS). Furthermore, using remote sensing data from different periods, a continuous melting of the icecap by about 3% per decade and a loss of about 16% of the area between 1942 and 2002 was documented. At the outlet glacier 'Glacíar Lengua' of Gran Campo Nevado an energy balance measuring station was operated in the ablation zone from February to April 2000 and the ablation was determined. It is shown that a very high mass turnover occurs, which in summer is mainly determined by the input of sensible heat. In contrast to Alpine glaciers, the radiation balance is only the second most important contribution to the energy balance. The flow velocity in the ablation zone was determined on the basis of repeated measurements over several years with GPS on the ablation stakes at about 65 m per year. From the measurement of ablation and energy balance, a degree day model was calibrated for Glacìar Lengua. With an average degree day factor of 7.01 mm/(day °C), we obtain between 7 m and 8 m of water equivalent (WEQ) ablation per year at 450 m a.s.l. in the ablation zone of the glacier. The deviation between the ablation measured on ablation stakes over several years and the ablation determined from the degree-day model with the data from AWS Gran Campo NPB is max. ±11% for the individual annual sections and averages about ±5%. Using the altitude gradients of precipitation and temperature and the terrain model of Glacíar Lengua, the degree day model was extended to the entire glacier surface. Corresponding to the high mass turnover, a very flat specific mass balance gradient is obtained, ranging from an ablation of about 12,000 mm WEQ ablation at the end of the tongue at 110 m a.s.l. to an accumulation of about 11,000 mm snow precipitation at 1600 m a.s.l. at the upper end of the catchment area. The analysis of the sensitivity of the mass balance to fluctuations in temperature and precipitation yields an average sensitivity of the mass balance to fluctuations in precipitation for oceanic climate. However, the sensitivity to fluctuations in air temperature can be described as extreme in a global comparison with other high oceanic locations. The reconstruction of the mass balance according to the derived sensitivity characteristics of the glacier with the aid of long time series of the monthly mean values of temperature and precipitation of the nearest stations and NCEP/NCAR grid points results in a predominantly negative mass balance since about 1960. In the period before that, after presumably positive mass balances in the first decades of the 20th century, between about 1940 and 1960, on average balanced to slightly positive mass balances were recorded. The modelled mass balance series reflects a slight warming trend of between half a Kelvin and one Kelvin in the second half of the 20th century in southwest Patagonia. : Habilitation thesis, University of Freiburg, Germany; research funded by the German Research Foundation under grant No. SCHN680/1-2 (DFG GEBRIS database project number 5306262, https://gepris.dfg.de/gepris/projekt/5306262)